Optimizing the Power Supply Planned Maintenance System With The Reliability Centered Maintenance (RCM) Method at PT. Pertamina EP Asset 4 Sukowati A Field - Eko Prastiyo; Rizky Stighfarrinata; Ardana Putri Farahdiansari (Journal of Social Science and Economics, 2022)
PT.Pertamina EP Asset 4 Sukowati A Field is an industry that never stops 24 hours for the continuity of the Oil and Gas production process. The process must require energy, one of the main ones is electrical energy which is used to supply power to production support equipment/machines. In the PT.Pertamina EP Asset 4 Sukowati A field, there are 3 Gensets, namely Genset 1 (125 KVA), Genset 2 (100 KVA) and Genset 3 (100 KVA) which are used to supply electrical energy. The three generators have a rather old operating age, often have problems with damage to their engine components, and the schedule for generator maintenance is also uncertain. The problem that becomes the object of this research is optimizing the power supply planned maintenance system with the RCM method at PT.Pertamina EP Asset 4 Sukowati A Field and identifying the comparison of power supply maintenance systems before and after using the RCM method. The purpose of this research is to optimize the power supply planned maintenance system with the RCM method at PT. Pertamina EP Asset 4 Sukowati A Field and identify comparisons before and after using the RCM method. The results of this study indicate that Gensets 1, 2, and 3 often experience downtime / failure in operation, because the machine tools are a bit old, as well as machine maintenance that has not been accurate and planned. With these conditions, the company needs the reliability of generator engine maintenance with the RCM method, so that the generator engine gets accurate and planned maintenance, so as to minimize downtime / failure in operation and also the previous generator engine maintenance is less accurate and planned, while maintenance with the RCM method is more efficient. accurate and planned.